ANALYSIS OF THE EFFECT OF GRANULAR TYPE AND MOISTURE CONTENT ON DYNAMIC ANGLE OF REPOSE IN A ROTATING CYLINDER - Adriel, Jonathan
Granular material is material that consists bunch of distinct and discrete macroscopic particles. The experiment of granular in rotating cylinder is a common experiment to study granular material behavior. In this study, we investigated the effect of granular type and moisture content on the dynamic angle of repose in a rotating cylinder. Marbles, rice seeds, mung beans, and sand are used as the samples. Experimental results show each sample has a different dynamic angle of repose that is related to the shape of the sample. In this study, the effect of the moisture content on the sand sample is also investigated. Experimental results show the addition of water content has no significant effect on the dynamic angle of repose. This occurs because the moisture content used has passed the critical point.